Der Tanz - Bie, Oskar 1864-1938 (Berlin Julius Bard, 1919)
In this volume, the author, music and art historian Oscar Bie (1864-1938) presents the rhythmic arts, 'das Fest der Elemente', dance in service, social dance, dance as a work of art, the ballet and music from a historical perspective. The lively and exuberant dances of the upper social classes of the 16th century were stylised adaptations of the dances of the lower classes. Dance schools at the most important European courts taught the nobility, so that the most popular dances could easily be transferred from one country to another. Skilled impresarios organised splendid performances in which dances, singing, recitation and pantomime were performed in a richly decorated setting. (Translated with DeepL.com)
Originally published in 1905. 3rd edition published in 1925
Ex libris Alfons Thijs (plate)
Keywords: Dance; Cultural history; Theater history; Fine art